The Use of PhET Media to Improve Elementary Students Ability to Solve Mathematics Problems - Rita Dwi Purwanti; Budi Usodo; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2025)
PhET Interactive Simulations were initially developed for science learning but have recently gained attention in mathematics education due to their potential to enhance students’ problem-solving skills. This research employs the Systematic Literature Review (SLR) method by collecting, reviewing, and analyzing relevant literature on the use of PhET media to improve mathematical problem-solving skills among elementary school students.. PhET media is known as an interactive simulation tool initially developed for science learning, but its use in mathematics education has begun to gain attention. This research employs the Systematic Literature Review (SLR) method by collecting, reviewing, and analyzing relevant literature on the use of PhET media to improve mathematical problem-solving skills among elementary school students. The study employs the Systematic Literature Review (SLR) method, systematically collecting, reviewing, and analyzing various relevant literature on the use of PhET media in enhancing mathematical problem-solving skills among elementary school students. PhET media is known as an interactive simulation tool initially developed for science learning, but its use in mathematics education has begun to gain attention. This research employs the Systematic Literature Review (SLR) method by collecting, reviewing, and analyzing relevant literature on the use of PhET media to improve mathematical problem-solving skills among elementary school students. The inclusion criteria consist of journal articles published between 2014 and 2024, focusing on the topic of PhET media and mathematical problem-solving skills in elementary school contexts, and accessible through databases such as Google Scholar, ERIC, and Scopus. The exclusion criteria include articles published before 2014, studies unrelated to mathematics learning or PhET media, and sources that are not peer-reviewed journal articles.The review results indicate that PhET media can increase students' active participation, help visualize abstract mathematical concepts, and encourage the application of more flexible and exploratory problem-solving strategies. The effectiveness of PhET also increases when combined with problem-based or inquiry-based learning approaches. These findings have positive implications for teachers and curriculum developers, suggesting the integration of interactive digital media into the mathematics learning process in elementary schools.